2015
DOI: 10.1016/j.febslet.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Double‐negative feedback loop between long non‐coding RNA TUG1 and miR‐145 promotes epithelial to mesenchymal transition and radioresistance in human bladder cancer cells

Abstract: a b s t r a c tLncRNAs have a critical role in the regulation of cellular processes such as cancer progression and metastasis. In the present study, we confirmed that TUG1 was overexpressed in bladder cancer tissues and established cell lines. Knockdown of TUG1 inhibited bladder cancer cell metastasis both in vitro and in vivo. Furthermore, we found that TUG1 promoted cancer cell invasion and radioresistance through inducing epithelial-to-mesenchymal transition (EMT). Interestingly, TUG1 decreased the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
131
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 36 publications
7
131
0
1
Order By: Relevance
“…3a–d). Intriguingly, the interaction between TUG1 and miR-145, which induced epithelial-to-mesenchymal transition through derepression of ZEB2, has been found in bladder cancer16. Consistently, RNA-FISH analysis revealed that numbers of TUG1 molecules were extremely abundant compared with those of miR-145 molecules in GSCs, whereas they were significantly increased by TUG1 inhibition (Fig.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…3a–d). Intriguingly, the interaction between TUG1 and miR-145, which induced epithelial-to-mesenchymal transition through derepression of ZEB2, has been found in bladder cancer16. Consistently, RNA-FISH analysis revealed that numbers of TUG1 molecules were extremely abundant compared with those of miR-145 molecules in GSCs, whereas they were significantly increased by TUG1 inhibition (Fig.…”
Section: Resultssupporting
confidence: 63%
“…Notably, as determined by RNA immunoprecipitation (RIP) analysis, both TUG1 and miR-145 bound to wild-type AGO2 but did not bind to a mutant form of AGO2 devoid of the PAZ domain, the latter serving as a module for si/miRNA transfer in the RNA silencing pathway and as an anchoring site for the 3′ end of guide RNA within silencing effector complexes (Supplementary Fig. 5c,d)1628.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previously published data, our findings suggest that Tug1 localizes to both the cytoplasm and the nucleus. While we have focused on the role of Tug1 in the nucleus in this study, it has been previously shown that cytoplasmic Tug1 could act as a competitive endogenous RNA (ceRNA) for certain miRs (60,61), as well as play a role in the translational stability of mRNAs (62). Further studies are needed to unravel the cytoplasmic function of Tug1 in podocytes and the interplay between cytoplasmic versus nuclear Tug1 in regulating mitochondrial bioenergetics.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of TUG1 may confer anticancer drug resistance to cancer cells by overactivation of the PIK3/AKT signaling pathway. Furthermore, TUG1 promotes cancer cell invasion, metastasis, and radioresistance by through inducing epithelial-to-mesenchymal transition [10,31]. These may partly explain why patients with high TUG1 expression have poor prognosis.…”
Section: Discussionmentioning
confidence: 99%